Electrical characteristics of interfacial barriers at metal—TiO2 contacts. (10th September 2018) - Michalas, L; Khiat, A; Stathopoulos, S; Prodromakis, T
Abstract: The electrical properties of thin TiO2 films have recently been extensively exploited with the aim of enabling a variety of metal-oxide electron devices: unipolar and bipolar semiconductor devices and/or memristors. In these efforts, investigations into the role of TiO2 as active material were the main focus; however, electrode materials are equally important. In this work we address this point by presenting a systematic quantitative electrical characterization study on the interface characteristics of metal-TiO2 -metal structures. Our study employs typical contact materials that are used both as top and bottom electrodes in a metal-TiO2 -metal setting. This allows an investigation of the characteristics of the interfaces as well as holistically studying an electrode's influence on the opposite interface, referred to in this work as the top/bottom electrodes inter-relationship. Our methodology comprises the recording of current–voltage ( I – V ) characteristics from a variety of solid-state prototypes in the temperature range of 300 K –350 K, and their analysis through appropriate modelling. Clear field- and temperature-dependent signature plots were also obtained, so as to shine more light on the role of each material as top/bottom electrodes in metal-TiO2 -metal configurations. Our results highlight that these are not conventional metal–semiconductor contacts, and that several parameters are involved in the formation of the interfacial barriers, such as the electrode's position (atop or below the film), the electronegativity, the interface states, and even the opposite interface electrode material. Overall, our study provides a useful database for selecting appropriate electrode materials in TiO2 -based devices, offering new insights into the role of electrodes in metal-oxide electronics applications.